1995
DOI: 10.1128/mcb.15.11.6118
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Rearrangement That Generates the TRK-T3 Oncogene Involves a Novel Gene on Chromosome 3 Whose Product Has a Potential Coiled-Coil Domain

Abstract: Oncogenic rearrangements of the NTRK1 gene (also designated TRKA), encoding one of the receptors for the nerve growth factor, are frequently detected in thyroid carcinomas. Such rearrangements fuse the NTRK1 tyrosine kinase domain to 5-end sequences belonging to different genes. In previously reported studies we have demonstrated that NTRK1 oncogenic activation involves two genes, TPM3 and TPR, both localized similarly to the receptor tyrosine kinase, on the q arm of chromosome 1. Here we report the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(182 citation statements)
references
References 34 publications
5
172
0
4
Order By: Relevance
“…Immunofluorescence experiments with anti-myc 9E10 antibodies (Figure 6b, top) showed that all the variant ING4 proteins are localized in the nucleus, similarly to the wild-type. As control, the lack of reactivity of mock-transfected cells, and the cytoplasmic localization of TFG-myc protein (Greco et al, 1995) are shown. Moreover, Western blot analysis of nuclear and cytoplasmic extracts from ING4-myc-transfected HEK293T cells showed that all the ING4 variants retain the capability to enter the nucleus (Figure 6b, bottom).…”
Section: Ing4 Alternative Splicing G Raho Et Almentioning
confidence: 99%
“…Immunofluorescence experiments with anti-myc 9E10 antibodies (Figure 6b, top) showed that all the variant ING4 proteins are localized in the nucleus, similarly to the wild-type. As control, the lack of reactivity of mock-transfected cells, and the cytoplasmic localization of TFG-myc protein (Greco et al, 1995) are shown. Moreover, Western blot analysis of nuclear and cytoplasmic extracts from ING4-myc-transfected HEK293T cells showed that all the ING4 variants retain the capability to enter the nucleus (Figure 6b, bottom).…”
Section: Ing4 Alternative Splicing G Raho Et Almentioning
confidence: 99%
“…TRK-T3 encodes a 68 kDa cytoplasmic protein displaying a constitutive tyrosine phosphorylation and capable to transform NIH3T3 mouse ®broblasts (Greco et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The T3/WT plasmid contains the TRK-T3 cDNA inserted into the pRC/CMV expression vector (Greco et al, 1995), which carries the neomycin resistance gene. The T3/Y291F mutant carries the mutation of Tyr291 to phenylalanine (F291) and was constructed by means of site-directed mutagenesis using an in vitro oligonucleotide mutagenesis system (Altered Sites in vitro Mutagenesis System, Promega).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…In the TRK-T3 oncogene, produced by a t(1;3) translocation, the NTRK1 TK domain is juxtaposed to sequences of the TFG gene (Greco et al, 1995), which encodes a protein of unknown function containing a coiled-coil domain, putative phosphorylation sites for PKC and CK2 and glycosylation sites (Mencinger et al, 1997;Mencinger and Aman, 1999). The TFG coiled-coil domain plays an important role in TRK-T3 activation and its consequent biological activity insofar as it mediates the dimerization leading to the ligand-independent tyrosine phosphorylation of the TK domain.…”
mentioning
confidence: 99%